Pengembangan dan Validasi Skala Employee Value Proposition: Multidimensional High-Order - S. Sugiyanto; Rahmi Lubis (Universitas Airlangga, 2026)
This study highlights the importance of developing a contextually relevant Employee Value Proposition (EVP) measurement tool in Indonesia. Data was collected from 558 employees and analyzed using a quantitative approach through EFA and CFA with a split-sample strategy. The results revealed that EVP is a multidimensional construct comprising eight aspects, which are hierarchically structured into two overarching dimensions: internal and external. The second-order CFA demonstrated excellent model fit (CFI = .991; TLI = .988; SRMR = .016), with 22 items retained as valid and reliable indicators. These findings provide empirical evidence that EVP is a robust and relevant construct, while also broadening the literature on EVP in non-Western contexts. The study contributes to human resource management practices by offering a reliable framework for designing recruitment, retention, and employee engagement strategies tailored to organizational and employee needs.